THE USE OF HOT-CHROME VANADIUM WHITE IRON FOR WOODCUTTING TOOLS - A. V. Alifanov (Литьë и металлургия)
It is established that for production of the wood-cutting tool (cutting elements of disk saws, milling and plane knifes, etc.) It is reasonable to use chrome-vanadium white cast iron which after processing by hot deformation approximates the high-speed steels and even firm alloys by its operational properties, at considerably lower cost.